Late Quaternary temperature variability described as abrupt transitions on a 1/f noise background - Rypdal, Kristoffer; Rypdal, Martin Wibe (Earth System Dynamics, 2016)
Published version. Source at http://dx.doi.org/10.5194/esd-7-281-2016 In order to have a scaling description of the climate system that is not inherently non-stationary, the rapid shifts between stadials and interstadials during the last glaciation (the Dansgaard-Oeschger events) cannot be included in the scaling law. The same is true for the shifts between the glacial and interglacial states in the Quaternary climate. When these events are omitted from a scaling analysis the climate noise is consistent with a 1=f law on timescales from months to 105 years. If the shift events are included, the effect is a break in the scaling with an apparent 1=f law, with > 1, for the low frequencies. No evidence of multifractal intermittency has been found in any of the temperature records investigated, and the events are not a natural consequence of multifractal scaling.